INFLUENCING FACTORS OF BANK EMPLOYEES' MOTIVATION AND ITS IMPACT ON EMPLOYEES' PERFORMANCE - Ali, A.R.S. Ibn; Haque, A S M Ahsanul; Nahar, Shamsun (American International Journal of Multidisciplinary Scientific Research, 2022)
In this globalization era, banking institutions are facing competition in the marketplace. The demands of the customers are changing immensely day by day. Integration and globalization have become closer and closer to every firm in the competitive market. The main purpose of this study is to determine the motivational factors of bank employees that are related to employees' performance in the working place. The study was qualitative and was conducted using different sources to find out the motivational factors and their impact on employee performance. The researchers focus on the intrinsic and extrinsic motivation of the employees. For this study, data have been collected from previous studies and different sources like the ABDC database, Scopus database, Emerald database, ABS database, Springer database, and previous banking profiles. The study showed that employee empowerment, job security, emotional intelligence, attractive compensation package, and training and development have a positive and significant impact on creating motivation among the employees, which creates better performance in work. Based on the findings of this study, the organization should provide another attractive motivational factor and change HR policies and procedures to create employee motivation. Recommendations were also made for improvement in a certain area, creating motivation for better performance of bank employees in Bangladesh.  JEL Classification Codes: M120, M150.